The stabilization of BAM neural networks with time-varying delays in the leakage terms via sampled-data control. Issue 2 (February 2016) - Li, Li; Yang, Yongqing; Lin, Guang
Abstract This paper is concerned with the stabilization of bidirectional associative memory neural networks with time-varying delays in the leakage terms using sampled-data control. We apply an input delay approach to change the sampling system into a continuous time-delay system. Based on the Lyapunov theory, some stability criteria are obtained. These conditions are expressed in terms of linear matrix inequalities and can be solved via standard numerical software. Finally, one numerical example is given to demonstrate the effectiveness of the proposed results .